2017
DOI: 10.3847/2041-8213/aa79f0
|View full text |Cite
|
Sign up to set email alerts
|

Critical Height of the Torus Instability in Two-ribbon Solar Flares

Abstract: We studied the background field for 60 two-ribbon flares of M-and-above classes during 2011-2015. These flares are categorized into two groups, i.e., eruptive and confined flares, based on whether a flare is associated with a coronal mass ejection or not. The background field of source active regions is approximated by a potential field extrapolated from the B z component of vector magnetograms provided by the Helioseismic and Magnetic Imager. We calculated the decay index n of the background field above the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 37 publications
7
57
2
1
Order By: Relevance
“…This is significantly different from the findings of Wang et al (2017), who reported these fractions as 85% and 15%, respectively, based on an event sample largely comprised of smaller flares (75% of their analyzed events were <M5.0).…”
Section: Decay Index and Flux Ratiocontrasting
confidence: 56%
See 3 more Smart Citations
“…This is significantly different from the findings of Wang et al (2017), who reported these fractions as 85% and 15%, respectively, based on an event sample largely comprised of smaller flares (75% of their analyzed events were <M5.0).…”
Section: Decay Index and Flux Ratiocontrasting
confidence: 56%
“…Cheng et al 2011;Wang et al 2017). Wang et al (2017) suggested an empirical relation of the form h crit 0.5 · d PC (cf. their Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the field strength for the eruptive flares was weaker than that for the confined events at the same heights. Wang et al (2017) found that the decay index increased monotonously with height in the majority (∼ 85%) of studied 60 flaring regions and reached the critical value for the torus instability (n c = 1.5) at significantly higher heights for confined flares than for eruptive ones. Saddle-like n-profiles in the other regions had significantly smaller values of n at the saddle bottom in confined flares than that in eruptive ones.…”
Section: Introductionmentioning
confidence: 84%